Halophytes as components of lawns under different soil salinity and human impact in the health resort “Ciechocinek” - Nienartowicz, Andrzej; Piernik, Agnieszka; Marcykiewicz, Joanna; Lis, Marta; Kunz, Mieczysław; Viglia, Silvio (Ecological Questions, 2011)
The comparison was performed on the flora of lawns located in the vicinity of three brine concentration towers in the Spa Park in the town of Ciechocinek. It was found that a different level of saline water inflow into the soil and a different use of these lawns are the main causes of the observed differences in the number and the species composition of halophytes and glycophytes. The possibility of determining the differences in the intensity of human impact on the studied systems was discussed, as well as the value of the Environmental Sustainability Index was determined through emergy analysis. Energy flow diagrams were prepared for two basic greenery management methods and salt production, which best differentiates the flora of the studied lawns.